MEDIA PEMBELAJARAN TEBAK KATA DAN DAMPAKNYA TERHADAP MAHARAH KALAM SISWA - Muhammad Dzakiruddin; Mohammad Nu'man (Hijai - Journal on Arabic Language and Literature, 2021)
The lack of habituation of maha>rah kala>m in arabic language learning needs to get special attention, especially at the level of madrasah ibtidaiyah class VI which in fact still occupies the age of children and requires the right approach in its development to deepen the habit of speaking Arabic. This study tries to offer the design of maha>rah kala>m learning through alternating word guessing methods to increase students' interest in speaking Arabic. This research is qualitative research with class action research approach. The data collection in this study was obtained by means of observation, questionnaire dissemination, and documentation. The data analysis uses descriptive analsis according to John Broades Watson's behavioristic stimulus theory. The results showed an increase in students' interest in arabic language which was originally only 48% to 55% reviewed from the level of nervousness, students' interest in methods, ease of methods, and the impact felt by students after practicing the alternating word guess. The existence of this study shows that alternating word guessing has a significant impact on students' learning.